2020
DOI: 10.3390/nu12113411
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Food Security Status and Sleep Disturbance among Adults: A Cross-Sectional Study in an Indonesian Population

Abstract: Background: The relationship between food insecurity and the experience of sleep disturbance has received little attention among researchers, although food insecurity is associated with poor physical and mental health globally. This study aimed to investigate the relationship between food security status and sleep disturbance among adults 20–64 years old. Methods: The study’s population-based sample included 20,212 Indonesian adults who participated in the fifth wave of the Indonesia Family Life Survey (IFLS5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…1), of which 318 records were screened after removing duplicates. Of these 318 records, 302 were excluded because they did not meet our inclusion criteria, resulting in nineteen eligible studies for full-text evaluation (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(37)(38)(39)(40)(41)(42) . Of these nineteen studies, ten were excluded because they were conducted on children (40) or adolescents (43) , provided insufficient data for inclusion in our analyses (37)(38)(39)41,42,44,45) , or used variable domains to measure FI (24) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), of which 318 records were screened after removing duplicates. Of these 318 records, 302 were excluded because they did not meet our inclusion criteria, resulting in nineteen eligible studies for full-text evaluation (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(37)(38)(39)(40)(41)(42) . Of these nineteen studies, ten were excluded because they were conducted on children (40) or adolescents (43) , provided insufficient data for inclusion in our analyses (37)(38)(39)41,42,44,45) , or used variable domains to measure FI (24) .…”
Section: Resultsmentioning
confidence: 99%
“…In general, available studies have reported positive associations between FI and poor sleep quality; however, results are less consistent on select sleep health outcomes, including sleep quality and duration [22][23][24][25][26][27]. To that end, Ding et al [22] and Jordan et al [25] have reported associations between FI and poor sleep quality across the mild to severe status.…”
Section: Introductionmentioning
confidence: 99%
“…People in Mahu Administrative country on Saparua Island nowadays tend to use rice as a source of household food security, not sago and sweet potatoes. This happens because apart from lifestyle changes, local food diversification is not developing (Isaura et al, 2020). Sago and sweet potatoes cannot be processed so they do not yet have the added value that allows community members to enjoy a variety of delicious and nutritious foods from non-rice foods.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic food insecurity is mainly due to persistent and long-term causes such as poverty. The impact of food insecurity on a person's life includes the potential for adverse physical or mental health outcomes (7,(14)(15)(16). Furthermore, the long-term disadvantage in socioeconomic status may also contribute to chronic food insecurity (17,18).…”
Section: Introductionmentioning
confidence: 99%